2008
DOI: 10.1091/mbc.e08-01-0094
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-mediated Induction of Cyclin E Sensitizes Growth-arrested Adipose Stem Cells to DNA Damage–induced Apoptosis

Abstract: The differentiation capacity of mesenchymal stem cells has been extensively studied, but little is known on cell cycle-related events in the proliferation and differentiation phases of these cells. Here, we demonstrate that exposure to cAMP-increasing agents inhibits proliferation of adipose stem cells (ASCs). This antiproliferative effect is associated with both reduced cdk2 activity and pRB phosphorylation. Concomitantly, however, the level of cyclin E markedly increases upon cAMP induction, indicating that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 80 publications
(113 reference statements)
1
32
0
Order By: Relevance
“…8A) or knocking down MEK or cyclin E by siRNAs (Fig. 8B) blocked the PGE 2 -mediated perinuclear recruitment of Beclin 1, indicating that cAMP-induced recruitment is dependent on both the MEK-ERK pathway and cyclin E. Having previously demonstrated that induction of cyclin E by cAMP in ASCs depends on activation of ERK, 16 we have been able to establish the sequence of events from elevation of intracellular cAMP levels to induction of autophagy (Fig. 9).…”
Section: Resultsmentioning
confidence: 70%
See 4 more Smart Citations
“…8A) or knocking down MEK or cyclin E by siRNAs (Fig. 8B) blocked the PGE 2 -mediated perinuclear recruitment of Beclin 1, indicating that cAMP-induced recruitment is dependent on both the MEK-ERK pathway and cyclin E. Having previously demonstrated that induction of cyclin E by cAMP in ASCs depends on activation of ERK, 16 we have been able to establish the sequence of events from elevation of intracellular cAMP levels to induction of autophagy (Fig. 9).…”
Section: Resultsmentioning
confidence: 70%
“…5B and C), which is in line with our previous results on cAMP-signaling in ASCs. 16 As a control of equal loading, the lysates were also analyzed for expression of total ERK and/or actin.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations